Antibody against V Antigen Prevents Yop-Dependent Growth of Yersinia pestis - Philipovskiy, Alexander V. (American Society for Microbiology, 2005)
The V antigen (LcrV) of the plague bacterium Yersinia pestis is a potent protective antigen that is under development as a vaccine component for humans. LcrV is multifunctional. On the bacterial surface it mediates delivery of a set of toxins called Yops into host cells, and as a released protein it can cause production of the immunosuppressive cytokine interleukin-10 (IL-10) and can inhibit chemotaxis of polymorphonuclear neutrophils. It is not known how these mechanisms of LcrV operate, what their relative importance is, when they function during plague, and which are critical to protection by antibody. This study investigated several of these issues. C57BL/6 mice, mice unable to express IL-10, or mice with the macrophage lineage eliminated were treated with a protective anti-LcrV antibody or a nonprotective antibody against YopM and infected intravenously by Y. pestis KIM5 or a strain that lacked the genes encoding all six effector Yops. Viable bacterial numbers were determined at various times. The data indicated that Yops were necessary for Yersinia growth after the bacteria had seeded liver and spleen. Anti-LcrV antibody prevented this growth, even in IL-10(−/−) mice, demonstrating that one protective mechanism for anti-LcrV antibody is independent of IL-10. Anti-LcrV antibody had no effect on persistence in organs of Y. pestis lacking effector Yops, even though the yersiniae could strongly express LcrV, suggesting that Yops are necessary for building sufficient bacterial numbers to produce enough LcrV for its immunosuppressive effects. In vitro assays showed that anti-LcrV antibody could partially block delivery of Yops and downstream effects of Yops in infected macrophage-like J774A.1 cells. However, cells of the macrophage lineage were found to be dispensable for protection by anti-LcrV antibody in spleen, although they contributed to protection in liver. Taken together, the data support the hypothesis that one protective effect of the antibody is to block delivery of Yops to host cells and prevent early bacterial growth. The findings also identified the macrophage lineage as one host cell type that mediates protection.